Characterization of horizontal air–water two-phase flow in a round pipe part I: Flow visualization. (November 2015) - Talley, Justin D.; Worosz, Ted; Kim, Seungjin; Buchanan, John R.
Highlights: Performed high-speed flow visualization in horizontal air–water two-phase flow. Identified mechanisms responsible for flow regime transitions. Turbulence-based mechanisms do not occur in densely packed regions. For higher liquid flow rates the bubbly flow profile peaking is reduced with increasing L/D. Plug bubble formation does not occur directly at the upper pipe wall. Abstract: As a part of characterizing the bubble interaction mechanisms and flow regime transition processes in horizontal gas–liquid two-phase flow, a flow visualization study is performed in an air–water test facility constructed from 3.81 cm inner diameter clear acrylic round pipes. The test section is approximately 250 diameters in length to allow for development of the flow. Flow visualizations are performed using a high-speed video camera at 80 and 245 diameters downstream of the inlet to observe the development of the flow structures. A total of 27 flow conditions including bubbly, plug, slug, stratified, wavy, and annular flows are characterized in the present study. In highly turbulent bubbly flow conditions it is found that the distribution becomes more uniform with increasing development length through a turbulence penetration process that counters the effect of buoyancy. It is also found that plug bubbles form below a layer of small bubbles rather than at the upper pipe wall where the bubbles are most packed. In fact, it is consistently found that turbulence-based bubble interactions do not occur in the most densely packed regions as the eddies there are not large enough to effect the bubbles. Rather, bubble packing-induced coalescence occurs in these regions and contributes to the formation of plug bubbles. The newly formed plug bubbles move faster than, and ultimately pass, the smaller bubbles above due to the effect of the wall. These small bubbles are subsequently overtaken by the following plug bubble and coalesce with the nose region through a process denoted as drag-induced coalescence.